Does successful project management equates to project success? - Wan Abdullah, Wan Maimun; Ramly, Ahmad (2006)
There have been many studies on the subject of project management and project success. Early studies in the mid 1900s linked project management and project success to the triple objectives of Time, Cost & Quality. As such it was concluded that, project management techniques have a significant impact on project success. Subsequently, by the turn of the century, it was pointed out that project management literature often confusingly equate project management success to project success as studies indicate that there are other dimensions to project success namely policy & strategy, team & leadership, stakeholder management, communication, financial resources, learning from experience, contracting, external environment, performance measurement baseline, innovation and contractor’s competence. Further researchers pointed out that there are two separate components of project success i.e. success criteria and success factors. This study conducted literature reviews in an attempt to list the variables to project success and a preliminary study was then carried out to identify the critical factors for project success.